2022
DOI: 10.3389/fpubh.2022.898043
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Air Pollutants and Their Effect on Multiple Sclerosis: A Review Study

Abstract: Toxic air pollutants are one of the main factors that have the effect of synergism to increase the incidence of multiple sclerosis (MS). This review aims to investigate the effects of toxic air pollutants on the occurrence of multiple sclerosis (MS). A narrative review of the literature was done from 2000 to 2022 based on various databases such as Google Scholar, Web of Science, Springer, PubMed, and Science Direct. In this study, according to the databases, three hundred and sixty articles were retrieved. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 108 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…This finding is in line with previous studies that highlighted the air pollution as a well-known environmental risk factor for MS ( 43 ). Mohammedi et al ratified this observation in a review that showed that inhalation of high concentration of toxic air pollutants can increase the risk of MS ( 44 ). Agricultural workers should be more vulnerable to MS.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous studies that highlighted the air pollution as a well-known environmental risk factor for MS ( 43 ). Mohammedi et al ratified this observation in a review that showed that inhalation of high concentration of toxic air pollutants can increase the risk of MS ( 44 ). Agricultural workers should be more vulnerable to MS.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Sclerosis (MS) is a chronic autoimmunerelated disease that impacts the central nervous system (CNS) and can result in extreme cognitive or physical disability and/or neurological deficiencies [5,6]. With MS, the CNS attacks the fatty myelin sheath covering of the neuron and interrupts the electrical signals between neurons in the brain.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…The new WHO guidelines specify six pollutants: particulate matter (PM), ozone (O₃), nitrogen dioxide (NO₂), sulfur dioxide (SO₂), and carbon monoxide (CO), as they are primarily linked to the worst health outcomes and environmental health impacts [6]. The risk associated with particulate matter equal to or smaller than 10 and 2.5 microns (µm) in diameter (PM₁₀ and PM₂.₅) is of particular public health relevance either in the short-term (acute) or long-term (chronic) exposure [8]. The smaller the size, the higher the penetration ability of the particles, invading the deepest parts of the lungs and more easily reaching the bloodstream, resulting in respiratory and cardiovascular effects and affecting other organs [9].…”
Section: Introductionmentioning
confidence: 99%